Effect of Vitamin A and Magnesium Supplementation on Consumption and Digestibility of Dry Matter and Organic Matter in Lamb - Jalalludin, Jalalludin; Suryapratama, Wardhana; Prayitno, Caribu Hadi (Universitas Bengkulu, 2025)
A study to determine the effect of vitamin A and magnesium supplementation on Dry Matter Digestibility (DMD) and Organic Matter Digestibility (OMD) in lamb. The research was conducted experimentally using a Randomized Completely Block Design (RCBD) using 18 rams local aged 7 - 8 months with an average initial body weight of 20 kg ± 2.38 kg. The feed was given at 4% Dry Matter (DM) of body weight with a ratio of ammoniated rice straw and concentrate of 25%:75%. The treatments tested were T0 (control), T1 (25% ammoniated rice straw, 75% concentrate, plus 2000 IU of vitamin A), and T2 (25% ammoniated rice straw, 75% concentrate, plus 2000 IU of vitamin A, plus 1 gram of magnesium). The results of the variance of the analysis showed that the treatment of vitamin A and Magnesium administration had a real effect (p<0.05) on the digestibility of organic matter, while other variables were not accurate. The average digestibility of organic matter was T0 at 91.49%, T1 at 91.19%, and T2 at 92.24%. T2 was the treatment with the highest digestibility, with a difference of 2.75% from the control treatment. After the Randomized Completely Block Design (RCBD) and Variance of Analysis test, the next test used Honestly Significant Difference (HSD). Vitamin A and Magnesium supplementation affected the digestibility of organic matter by 2.75% higher than the control treatment.